2015
DOI: 10.1016/j.celrep.2015.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Aggregation of Alpha-Synuclein and Selective Degeneration of Lewy Inclusion-Bearing Neurons in a Mouse Model of Parkinsonism

Abstract: Summary Aggregated alpha-synuclein inclusions are found where cell death occurs in several diseases, including Parkinson’s Disease, Dementia with Lewy Bodies and Multiple System Atrophy. However, the relationship between inclusion formation and an individual cell’s fate has been difficult to study with conventional techniques. We developed a system that allows for in vivo imaging of the same neurons over months. We show that intracerebral injection of preformed fibrils of recombinant alpha-synuclein can seed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
222
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 37 publications
25
222
2
3
Order By: Relevance
“…The numbers of aggregates required for ROS production are therefore two orders of magnitude lower than what is required for the templated seeding, and this difference suggests that the templated seeding by the oligomers occurs less readily than the cellular damage caused by the aggregates themselves. This idea is consistent with the long-established link between oxidative stress and neurodegeneration (49) and the fact that the oxidative reactions can promote the aggregation of αS (50), and it is corroborated by experimentally observed correlation between αS seeding and cellular toxicity (15). Based on our findings, we hypothesize that for small aggregates in vivo, if templated seeding occurs, it is under conditions of raised levels of ROS, which in turn may promote αS aggregation, resulting in the aggregate spreading in a cell-driven way that does not strongly depend on the seeding effectiveness, as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The numbers of aggregates required for ROS production are therefore two orders of magnitude lower than what is required for the templated seeding, and this difference suggests that the templated seeding by the oligomers occurs less readily than the cellular damage caused by the aggregates themselves. This idea is consistent with the long-established link between oxidative stress and neurodegeneration (49) and the fact that the oxidative reactions can promote the aggregation of αS (50), and it is corroborated by experimentally observed correlation between αS seeding and cellular toxicity (15). Based on our findings, we hypothesize that for small aggregates in vivo, if templated seeding occurs, it is under conditions of raised levels of ROS, which in turn may promote αS aggregation, resulting in the aggregate spreading in a cell-driven way that does not strongly depend on the seeding effectiveness, as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, transplanted embryonic neurons in patients with PD developed LB deposits, suggesting that these aggregates can spread (11). Experiments in wild-type and transgenic mice showed that injection of fibrils of recombinant αS could lead to the aggregation of the endogenous protein, supporting this concept (12)(13)(14), and the selective fate of the aggregate-containing neurons was demonstrated (15). Although the pathological spreading of αS has now been reproduced in many laboratories, the molecular mechanism of the observed phenomenon is not fully understood and this is important for rational development of therapies.…”
mentioning
confidence: 56%
“…The inclusions formed could be classified depending on their localization in the cell. Neuritic and perykarial inclusions have also been observed by others (49,51,57) and colocalize with Hsp90, resembling pathology-related aggregates (40). These inclusions are formed by both endogenous aSyn and internalized recombinant species.…”
Section: Discussionmentioning
confidence: 74%
“…Cite this article as Cold Spring Harb Perspect Biol 2017;9:a023523 recent article that describes long-term surveillance of deposition sites containing aggregated a-synuclein indicated that over time these deposits are associated with cell death (Osterberg et al 2015). This apparent contradiction can be explained by at least two models.…”
Section: Protein Quality Control In Health and Diseasementioning
confidence: 89%